Malawi - Gender-Based Violence Assessment : Scope, Programming, Gaps and Entry Points - World Bank (Washington, DC, 2022)
The objective of this assessment is to provide background information about GBV issues, policies, programming, and gaps in Malawi, for the purpose of assisting the World Bank (WB) to 1) consider how to directly support efforts to address GBV in Malawi; 2) inform strategies for integrating attention to GBV in development programming; and 3) understand the extent of GBV response programming. In addition to providing an overview of data on the scope of GBV in Malawi, the assessment investigates: legislative and policy protections related to GBV; systems and coordination mechanisms in place for addressing GBV in Malawi; and GBV response and prevention programming. The assessment analyzes key gaps across these areas of investigation based on inputs from key stakeholders as well as the desk review and concludes with several recommendations for WB to consider assisting in addressing these key gaps.